Benchmarking Study of Ballistic Current Transport Equations in Symmetric Double-Gate nano-MOSFET by Using Numerical Calculations and Simulation - Chek Yee, Ooi (Applications of Modelling and Simulation, 2023)
Five electron transport models for drain current equations of symmetric 10 nm Silicon-based (Si-based) double-gate (DG) nano-MOSFET have been numerically investigated in this paper. All these models are based on ballistic transport flow. The first model, named full ballistic model, assumed no backscattering to the source and produced an on-state drain current of 1.137x103 μA/μm. The second model, named electrostatic model which based on electrostatic, included scattering and produced on-state drain current of 2.182x103 μA/μm. Whereas the third model, named flux-theory model, and fourth model, named flux-theory corrected model, were analyzed using flux-theory concept of electron flow and then two different drain current equations were obtained. However, both models producing almost the same value of on-state drain current 2.548x103 μA/μm numerically. Finally, the fifth model, named space charge model, utilized the concept of subband and electron charge distribution on k-space, producing on-state current of 2.241x103 μA/μm. All these models treat electron flow quantum mechanically. Thus, all five computed on-state currents were benchmarked against an on-state current simulated using online device simulator nanoMOS which outputted Si-based ultra-thin channel nano-MOSFET norminal on-state drain current of 2.500x103 μA/μm. The flux-theory models are found to be the most compatible to simulation result because flux-theory model can be generalized for multi-subband, various materials and arbitrary wafer orientations. On the other hand, the first model without backscattering consideration exhibited the least accurate result due to the fact that scattering cannot be ignored in formulating quantum ballistic transport models. The accuracy of this benchmarking evaluation showed that highly sophisticated electron transport numerical models must incorporated ballistic quantum nature effects as well as scattering effects when developing commercial device simulation tools such as TCAD.